Bahasa Arab: “Ruh” Pendidikan Islam - Adhriansyah A. Lasawali (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2020)
This research examines the urgency (benefits) of Arabic for Islamic education. After the researchers studied and analyzed, Arabic is a very important language to learn in understanding Islamic education. This is not only because the Arabic language is the language of the holy book of Islam (the Qur'an) and the Hadith of the Prophet Muhammad, but more than that, this language is used in books and as the source of Islamic teachings, such as fiqh, hadith, ulumul qur'an, tafsir, tauhid and so on. In other words, Arabic is the language of